PENGEMBANGAN MEDIA PEMBELAJARAN BETANG EDU BERBASIS ANDROID PADA MATERI TOLERANSI DAN MENGHARGAI PERBEDAAN - Nova Nur Aini; Muhammad Rifaldi; Afda Yulistiana; Abdul Azis (ADIBA : JOURNAL OF EDUCATION, 2024)
The development of mobile technology opens up opportunities for innovation in Islamic Religious Education (PAI) learning, especially in the material of tolerance and respect for differences. This research aims to develop and test the feasibility of the Android-based learning media "Betang Edu Application" for class IX students at SMPN 8 Palangka Raya. Using the Research and Development (R&D) method with a 4D model, this research involves the Define, Design, Development and Dissemination stages. Product validation was carried out by media experts and material experts using a Likert scale instrument. The research results show that the Betang Edu application is considered feasible by media experts with a percentage of 76.6% and is considered very feasible by material experts with a percentage of 82.22%. The app offers interactive content relevant to the local context, increasing students' understanding of tolerance and respect for differences. This research contributes to the development of innovative PAI learning media, combining technology with local cultural values, and supporting the cultivation of tolerance in the digital era.